Effect of Toxoplasmosis Infection on Liver and Kidney Functions among Pregnant Women in Abo-Gharib District- Iraq - Al-Jowari, Suha; Hussein, Dina (Iraqi Journal of Science, 2023)
The effect of toxoplasmosis infection on liver and kidney functions among pregnant women in Abo-Gharib District- Iraq was studied. Forty women that had positive test for toxoplasmosis by ELISA test were participated in this study. Also control group of apparently healthy women was selected (ten total women). This group had negative test for toxoplasmosis (ELISA test). The venous blood was collected from each patient and control individual to obtain serum. Liver function was evaluated by the estimation of serum aspartate aminotransferase (AST/GOT), serum alanine aminotransferase (ALT/ GPT) and serum alkaline Phosphatase (ALP) activities. Kidney function was evaluated by the estimation of serum creatinine and urea concentrations by the enzymatic methods.The results show that there is a significant (P< 0.05) increase in the means of AST, ALT and ALP activities as well as urea and creatinine concentrations in the serum of toxoplasmosis women compared with control group.In conclusion, this study indicates that toxoplasmosis affects liver and kidney functions as evidenced by the significant increase in the levels of some biochemical parameters in patients group; this may possibly affect some specific enzyme systems, which can, consequently, exhibit serious pathology, including hepatitis, pneumonia, blindness and severe neurological disorders.